2023
DOI: 10.1093/bjc/azac094
|View full text |Cite
|
Sign up to set email alerts
|

Making Desistance Recognizable: How Ex-Offenders Can Signal Their Desistance From Crime to Employers by Strategic Design

Abstract: One of the primary concerns employers hold about hiring an ex-offender is the potential reoffending risk they pose. However, criminological literature shows that an ex-offender may be able to mitigate employers’ concerns by signalling their desistance from crime. Less understood is how ex-offenders can signal their desistance to (a) make desistance recognizable and (2) communicate desistance signals that employers value. This article draws on the results from the second phase of an Explanatory Sequential Mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In a synthesis of signaling theory's use in management literature, Connelly et al (2011) noted that the value of a signal is in part dependent on the perceived honesty and reliability of the signaler. Employer beliefs that colleges/universities are reliable, honest assessors of an applicant may be eroded or overridden if these same employers do not similarly believe in the honesty and reliability of prisons (for a discussion regarding honesty and reliability in the context of desistance signaling, see Reich, 2023). Santos et al (2023) found some evidence to suggest that the signaling potential of credentials can be complicated by their affiliation with prison.…”
Section: Postsecondary Carceral Education-an Untested Positive Creden...mentioning
confidence: 99%
See 1 more Smart Citation
“…In a synthesis of signaling theory's use in management literature, Connelly et al (2011) noted that the value of a signal is in part dependent on the perceived honesty and reliability of the signaler. Employer beliefs that colleges/universities are reliable, honest assessors of an applicant may be eroded or overridden if these same employers do not similarly believe in the honesty and reliability of prisons (for a discussion regarding honesty and reliability in the context of desistance signaling, see Reich, 2023). Santos et al (2023) found some evidence to suggest that the signaling potential of credentials can be complicated by their affiliation with prison.…”
Section: Postsecondary Carceral Education-an Untested Positive Creden...mentioning
confidence: 99%
“…Bushway and Apel (2012) were the first to apply signaling theories to the reentry context, suggesting that for formerly incarcerated individuals, credentials may also signal desistance to potential employers who have imperfect information regarding an applicant's likelihood to re‐engage in criminal behavior. As predicting an individual's likelihood to reoffend directly after release is difficult and error prone (Bushway et al., 2009; Gottfredson & Moriarity, 2006), scholars have begun to consider how best to “make desistance recognizable” to employers (Reich, 2023, p. 1274). Some evidence suggests that positive credentials may provide an effective way of doing so; in an experimental survey, Denver and DeWitt (2023) found that, to varying degrees, the impact of reference letters, occupational licenses, and voluntary job training programs on hireability were mediated by respondents’ perceptions of the applicants’ general recidivism risk, workplace risk, and trustworthiness.…”
Section: Postrelease Employment and Positive Credentialsmentioning
confidence: 99%
“…Second, even though those individuals may have had positive experiences with criminal justice professionals (e.g., probation officers or prison program supervisors), whether their reference would be perceived as a positive credential is unclear. A qualitative study by Lindsay (2022, see also Reich, 2023) found that formerly incarcerated individuals often face a “prison credential dilemma” as they believe prospective employers may perceive credentials obtained in prison as a negative signal that underscores their risk. Therefore, formerly incarcerated individuals are strategic about how they present their prison credentials on job applications.…”
Section: Literature Reviewmentioning
confidence: 99%